An evolutionary perspective on zinc uptake by human fungal pathogens1. Issue 6 (10th June 2015) - Wilson, Duncan
<x xml:space="preserve">Abstract</x> A link between environmental pH and fungal zinc uptake strategies? Soil acidity and endemic mycoses in the USA.